SURVIVAL ANALYSIS OF NASOPHARYNGEAL CARCINOMA IN HASAN SADIKIN HOSPITAL - Riska Adriana; Yussy Afriani Dewi; Dindy Samiadi; Edo Wira Candra (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Abstract Introduction: Nasopharyngeal carcinoma (NPC) is the fifth in range of malignancies in Indonesia and has high morbidity and mortality. A survival rate is a statistical index that summarizes the probable frequency of specific outcomes for a group of patients at a particular point in time. The survival of patients with nasopharyngeal carcinoma is influenced by several factors, such as the patient and tumor. Objective: The objective of this research is to determine survival analysis and factors that influence nasopharyngeal carcinoma which recorded at Hasan Sadikin Hospital. Methods: It is an analytic observational study. Data were analyzed with survival analysis using the Cox Regression test. Result: The subjects were 215 patients who were diagnosed NPC in first time at Hasan Sadikin Hospital from January 2006 until December 2009. There was a significant correlation between age, staging, histopathologic type and therapy with the survival (P=0.0001), (P=0.026), (P=0.0001), (P=0.024), (P=0.003); but no significant correlation between gender with the survival. Based on Cox proportional hazard, the male patients in over fifty years old have a risk of the death 7.724 and 1.113 times. The patients with nasopharyngeal carcinoma type I have a risk of the death 2.381 times. The patients with stage IVC have a risk of the death 3183.9 times. The patients who underwent chemoradiation have a risk of the death 2.761 times. Conclusion: The survival of patients with nasopharyngeal carcinoma is most influenced by prognostic factors such as age and therapy.